Elevated expression of APOO as a potential prognostic marker in breast cancer: insights from bioinformatic analysis and experimental validation - Yang Bai; Qian Tang; Liang Zheng; Jun He; Wenjian Wang; Liqi Li; Ju Yu (BMC, 2024)
Abstract Objective Apolipoprotein O (APOO) has been identified through bioinformatic prediction analysis as being highly expressed in various tumors, including breast cancer (BRCA). However, further investigations are required to understand and confirm APOO's biological role in BRCA. Methods Bioinformatic analyses were employed to identify genes' expression statuses and their relationship with the prognoses of patients. The genes' functions were determined in cell line by gain or loss of function assays. Mechanistic studies were carried out by western blot. Results Our study reveals a correlation between increased APOO expression and poorer clinical outcomes in BRCA patients. The diagnostic value of APOO was demonstrated by Receiver Operating Characteristic (ROC) curve analysis, showing a notable area under the curve (AUC) of 0.937. Additionally, we observed that APOO knockdown impedes cell proliferation and migration. Gene Set Enrichment Analysis (GSEA) suggests that APOO expression is associated with the regulation of apoptosis and autophagy signaling pathways. Experimentally, modifying APOO expression in vitro influenced apoptosis and autophagy in BRCA cells. In conclusion, our findings indicate a significant link between APOO expression and BRCA progression, mediated through APOO's impact on cellular apoptosis and autophagy. Conclusions Our data show that APOO controls BRCA process through apoptosis and autophagy signal pathway, which might provide multiple promising choices for the treatment of BRCA.